User Interface Design for Doctor Reservation Website using Design Thinking Method - Azelia Puspa Diah Narendri; Ariq Cahya Wardhana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
In the current era of digital transformation, the rapid integration of healthcare services is crucial to meet patient expectations and improve service delivery. Klinik Putri faces challenges such as long queues and difficulties in booking doctor appointments, which negatively impact patient satisfaction. This study aims to design a user-friendly, web-based doctor reservation system using the Design Thinking methodology, which consists of five stages: empathize, define, ideate, prototype, and test. Usability testing was conducted using the System Usability Scale (SUS), a standardized tool for evaluating system usability. The results showed an average SUS score of 83, placing the system in the “acceptable” category, Grade B, and receiving an “excellent” rating according to the Adjective Rating scale. These findings demonstrate that the proposed website design effectively addresses user needs, enhances the user experience, and contributes to improving the efficiency of healthcare services at Klinik Putri.